The Relationship between Discipline, Responsibility, and Motivation Study to Study Achievement - Haryanto, Ery; Sulaiman, Sulaiman; Kusuma, Donny Wira Yudha (Journal of Physical Education and Sports, 2019)
The success reference indicator of the student in the study, it is looked from the study achievement. This research will study an intrinsic factor of student’s motivation, responsibility, and discipline. The objective of this research is to understand how much the influence of discipline, responsibility, and motivation to the study achievement. The research uses the quantitative correlational method. The object of this research is all of the student grade X at science and social studies in Public Senior High School 1 Grobogan who have not through the criteria score; they are 132 students. It has 36 man students and 96 woman students. The result is it has influence between discipline to study achievement, the responsibility to study achievement, motivation to study achievement, discipline, and responsibility to study achievement, discipline, and motivation to study achievement, responsibility, and motivation to study achievement, and discipline, responsibility, and motivation to study achievement. The great invention is if students have an advanced discipline, responsibility, and motivation, they will have a good study achievement and the opposite. It will be better if parents always give motivation, discipline, and responsibility orally or action, so the achievement of students is better.